Identifying and Exploring Sources of Knowledge Spillovers in European Union: Evidence from Patenting Data - Karkalakos, Sotiris (SPOUDAI Journal of Economics and Business, 2011)
Although the process of innovation is a crucial aspect of economic growth, there is less clarity about the measurement of economically useful ideas. Determining the extent to which different types of institutions contribute to the creation of new knowledge is essential for a deeper understanding of the dynamics involved. Using a spatial econometric framework, this article examines the productivity of knowledge and notes that the changes in productivity appear to correlate to the spatial distribution of new knowledge creation. The channels and the relationships through which knowledge can flow between different sources are identified and estimated. JEL Classification: O31, H41, O40, D24